Antimalarial primaquine for spinal sensory and motor blockade in rats. (9th August 2021) - Chou, An-Kuo; Chiu, Chong-Chi; Wang, Jhi-Joung; Chen, Yu-Wen; Hung, Ching-Hsia
Abstract: Objectives: The purpose of the experiment was to estimate whether intrathecal antimalarial drugs could provoke spinal block, and their comparison with lidocaine. Methods: Rats were intrathecally administrated with antimalarial agents (primaquine, chloroquine, hydroxychloroquine and amodiaquine) and lidocaine, and neurobehavioural examinations (nociception, proprioception and motor function) were assessed; n = 8 per group. One-way and two-way analysis of variance were designed to analyse data. Key findings: At a concentration of 20 mM, primaquine (0.46 mg/rat) exhibited the longest duration and the most potent effect of nociceptive, proprioceptive and motor blockade ( P < 0.01) among five drugs, whereas the other antimalarial drugs displayed a lesser or similar potency of spinal blockade compared with lidocaine (0.29 mg/rat). In dose-dependent studies, primaquine was more potent ( P < 0.01) than lidocaine for spinal block. At ED25, ED50 and ED75 equipotent doses, primaquine produced a greater duration of spinal motor, proprioceptive and nociceptive blockade when compared with lidocaine ( P < 0.01). Conclusions: Primaquine, chloroquine, hydroxychloroquine and amodiaquine produced spinal blockade. Primaquine was more potent and displayed a prolonged life of local anaesthetic effect compared with lidocaine, whereas the other antimalarial drugs displayed a lesser or similar potency compared with lidocaine.